Paternidade: um estudo psicanalítico sobre pesquisas desenvolvidas no contexto brasileiro - Prado, Juliana de Castro [UNESP] (2013)
The present study is an historical investigation about Brazilian psychoanalytic publications related to the Fatherhood in Brazil during the last three decades. This research consists of quantitative and qualitative studies regarded to the intellectual production of fatherhood in Brazil, taking into consideration not only what is being published about this subject, but also considering the way this subject is being elaborated by Brazilian authors. It was possible to verify with this study that the father is still responsible for the mother-son relationship prohibition, considered his symbolic function by Psychoanalysis, and also important to introduce the individual in society and culture. According to Freud and Lacan’s Psychoanalysis, fatherhood is associated to the paternal function, not necessarily being connected to the male character, but to its symbolical function of the Name of the Father, active metaphor in the incest prohibition, and the insertion of the individual in the Law and culture. As result from all the changes that the family configuration has suffered over the years, the picture of the father is found in process of transformation. Everything seems to be changing to a model of a nurturing father once fatherhood has been seen as an exchanging between the maternal and paternal functions